2008
DOI: 10.1097/01.ogx.0000334735.13818.9a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microarray-Based Detection Rates for Cytogenetic Abnormalities in Prenatal and Neonatal Specimens

Abstract: The mechanisms underlying cervical insufficiency, a cause of spontaneous second-trimester abortion and early preterm birth, remain poorly understood. There is, however, evidence that amniotic fluid (AF) infection is a key factor in pregnancy outcomes and postoperative complications. This study was an attempt to determine the frequency and clinical importance of intraamniotic inflammation in 52 patients with acute cervical insufficiency, defined as cervical dilation of 1.5 cm or more. The patients, seen at 17 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 0 publications
4
36
0
1
Order By: Relevance
“…There was a decrease in the number of uncertain cases from the Sahoo et al (2006) study [30] to the Shaffer et al (2008) study [31]. Besides differences in the design of the platforms, this may also reflect more experience gained from analysis of more postnatal cases.…”
Section: Future Issues For Prenatal Diagnostic Studies Using Acghmentioning
confidence: 78%
See 2 more Smart Citations
“…There was a decrease in the number of uncertain cases from the Sahoo et al (2006) study [30] to the Shaffer et al (2008) study [31]. Besides differences in the design of the platforms, this may also reflect more experience gained from analysis of more postnatal cases.…”
Section: Future Issues For Prenatal Diagnostic Studies Using Acghmentioning
confidence: 78%
“…These include a validation study with 51 samples [28], and 580 samples (AF and CVS) in four prospective studies [29][30][31][32]. The first published study was a validation study using cultured amniocytes from 21 samples on a targeted BAC array (otherwise, ∼ 10 Mb resolution) and on an array with a 1 Mb resolution (but not targeted for all microdeletion/microduplication syndromes or pericentromeric or subtelomeric regions) [28].…”
Section: Review Of Published Prenatal Acgh Studies For Detection Of Cmentioning
confidence: 98%
See 1 more Smart Citation
“…For the remaining 16 cases (34.8%), parental testing was offered for better interpretation. Subsequently, using a targeted clinical array, Shaffer Review et al reported two clinically significant changes by aCGH in 151 prenatal cases (1.3%) undergoing genetic testing for a variety of prenatal indications [84]. Coppinger et al compared the results from 182 cases analyzed on whole-genome BAC and oligonucleotide arrays to those of 62 cases analyzed on targeted BAC arrays.…”
Section: Standard Prenatal Indicationsmentioning
confidence: 98%
“…Les résultats préliminaires sont très contradictoires avec des taux d'anomalies variant de 2 à 50 %, selon que les aneuploïdies avaient ou non été exclues de l'étude, ou selon qu'il y avait ou non la présence de signes d'appel échographiques [41][42][43][44]. Ces études ont été réalisées soit sur liquide amniotique natif [45] soit après culture cellulaire.…”
Section: Quelle Utilisation En Diagnostic Prénatal ?unclassified